KECEPATAN PERTUMBUHAN DAN AKTIVITAS ENZIM LIGNIN PEROKSIDASE ISOLAT KAPANG LIGNOSELULOLITIK DALAM UPAYA PENANGGULANGAN SAMPAH ORGANIK LIGNOSELULOSA - Febriyanti, Elisa; Periadnadi, Periadnadi; Nurmiati, Nurmiati (Metamorfosa: Journal of Biological Sciences, 2017)
Research on the mycelial growth of mold isolates lignocelulolitic done using media substrate bran and sawdust. This research was conducted from April 2015 through March 2016 in the laboratory of Microbiology/ Mycology Department of Biology, Faculty of Mathematics and Natural Sciences, University of Andalas. This study aimed to compare the media effectively to the growth of mold isolates lignoselulolitik and lignin peroxidase (LiP) activity it generates in the response to the lignocellulosic organic waste. Comparison of media composition adapted to the treatment used is Bran 100%: Sawdust 0%; Bran 75%: Sawdust 25%; Bran 50%: Sawdust 50%; Bran 25%: Sawdust 75% and Bran 0%: Sawdust 100%. Parameters include the observation of mold growth on medium speed baglog and lignin peroxidase (LiP) activity was measured using a spectrophotometer at a wavelength of 310 nm with Veratryl Alcohol as a substrate. The results showed that the ratio of the bran media effectively : sawdust against mycelial growth of mold isolates are on treatment lignoselulolitik bran 75% : sawdust 25%, while the activity of lignin peroxidase (LiP) at the highest bran ratio of 50% : 50% sawdust.
Keywords: speed of growth, lignocellulolitic mold isolates, lignin peroxidase, organic waste